The Effect of Active Strategy of Students' Question Types on Critical Thinking Skills - Magfirah, Andi Husna; Hiola, Siti Fatmah; Palennari, Muhiddin; Muis, Abd; GH, Muliana (Biology Teaching and Learning, 2025)
Abstract. The study aims to determine the effect of the active strategy type Questions Student Have on critical thinking skills. The type of research consists of a quasi-experiment. The research design consists of a pretest-posttest control group design. The population of all students in grade X of SMA Negeri 22 Makassar consists of 5 classes with a total of 180 students. The sample selection was carried out randomly so that class X.2 (experimental) and class X.5 (control) were selected. Data analysis techniques consist of descriptive and inferential statistics. The results of the descriptive statistical analysis of the critical thinking test score of 49.61 are in the less category while the learning outcomes score of 79.31 are in the very high category. The results of the normality test of the sig. data value> 0.05, so that the data on students' critical thinking skills are normally distributed. The results of the homogeneity test of the sig value Based On Mean> 0.05 so that it is declared homogeneous. The results of the hypothesis test of the Sig value 0.001 <0.05, then Ho is rejected and H1 is accepted so that there is an effect of the Questions Student Have type strategy on critical thinking skills. The conclusion is that the active strategy type Questions Student Have can encourage students to be more active in participating in the learning process.Key words: Type of Questions Students have, critical thinking, quantitative research, descriptive analysis, inferential analysis.